Chinese cultural landscapes: from the ideal of a balanced bond between humans and nature to ecological forms of life - Yan Xu (Trans/Form/Ação, 2024)
Thus far, human development has been achieved at the cost of the destruction of cultural landscapes. With advent of industrial civilization, people have gained happiness and conveniences, but also confronted various cultural landscape predicaments. Environmental philosophy, a contemporary philosophy that regards the relationship between humans and nature as a fundamental issue, has focused on the protection of cultural landscapes. An analysis of ancient Chinese environmental philosophy demonstrates that ancient thinkers cared about everything in heaven and earth, and explored issues, such as a harmonious development between humans and nature, offering a novel approach to the preservation of Chinese cultural landscapes. Using Taoist environmental philosophy as an exemplar, this article provides a preliminary analysis of the definition of cultural landscapes, development of environmental philosophy and Taoist environmental philosophy. Building upon this foundation, it explores the role of environmental philosophies, such as “unity of heaven and man” in construction of ecological civilization, providing fresh perspectives for cultural landscape conservation.